Successful pregnancy in a high-risk catecholaminergic polymorphic ventricular tachycardia patient - Inmaculada Mejía Jiménez; Olga Villar Ruiz; Ana Sabín-Collado; María Valverde Gómez; Elena Montañés Delmás; Rafael Salguero Bodes (Perinatal Medicine Foundation, 2022)
Objective: To report the case of a successful pregnancy outcome in a severely symptomatic woman affected by catecholaminergic polymorphic ventricular tachycardia (CPVT) carrier of a novel variant in ryanodine receptor 2 (RYR2) followed by a review of the current literature. Case(s): A 27-year-old primigravida affected by CPVT was referred to our tertiary care hospital after an implantable cardioverter defibrillator (ICD) shock. The patient also received medical treatment with metoprolol and flecainide. A healthy baby was born by Cesarean section at 31 weeks after the onset of preterm labor and premature rupture of membranes. CPVT is a rare inherited cardiac condition characterized by episodic polymorphic ventricular arrhythmias with a structurally normal heart. These are usually triggered by exercise or emotional stress and can lead to syncope or even sudden cardiac death. Treatment of this condition comprises betablockers in isolation or in addition to other antiarrhythmics, left cardiac sympathetic denervation and/or ICD. Conclusion: This case illustrates the importance of a multidisciplinary approach in this clinical scenario and the benefits of an optimization of the medical treatment, and demonstrates that, even in severely affected patients, a successful pregnancy is possible under close control. However, the risk of arrhythmic events and the course of pregnancy remain largely unknown in patients with CPVT, and further investigation is needed.